SideSight: multi-"touch" interaction around small devices - Butler, Alex; Izadi, Shahram; Hodges, Steve (Proceedings of the ACM Symposium on User Interface Software and Technology (UIST '08), 2008)
Interacting with mobile devices using touch can lead to fingers occluding valuable screen real estate. For the smallest devices, the idea of using a touch-enabled display is almost wholly impractical. In this paper we investigate sensing user touch around small screens like these. We describe a prototype device with infra-red (IR) proximity sensors embedded along each side and capable of detecting the presence and position of fingers in the adjacent regions. When this device is rested on a flat surface, such as a table or desk, the user can carry out single and multi-touch gestures using the space around the device. This gives a larger input space than would otherwise be possible which may be used in conjunction with or instead of on-display touch input. Following a detailed description of our prototype, we discuss some of the interactions it affords.